Oleogels from Watermelon Rind Extract and Orange Peel Essential Oil for Hair Nutrition - Erlina, Iis; Fadilah, Nisa Lelita; Yulianti, Dwi Indah; Adiba, Asfiah; Febriany, Retno Putri; Ilmiawati, Auliya (EduChemia: Jurnal Kimia dan Pendidikan, 2024)
Watermelon rind extract is rich in protein, citrulline, and lycopene, whereas orange peel essential oil contains vitamins A, C, and E. Both ingredients have demonstrated potential in preventing hair loss. This study aimed to develop an oleogel that combines these two components to address hair loss. The efficacy of the oleogel for promoting hair growth was evaluated in male DDY (Deutchland Denken Yonken) mice. The oleogel characteristics, including pH, viscosity, color, homogeneity, oil binding capacity, spreadability, and organoleptic evaluations, were assessed through physical quality tests. Organoleptic analysis was conducted with 30 respondents from IPB University to identify the most preferred oleogel formulation. The yield of watermelon rind extract was 28.88%, while the orange peel essential oil constituted 2% (v/w) of the formulation. The optimal oleogel contained 3% watermelon rind extract and 1% orange peel essential oil, resulting in 100% hair growth in the mice. All the formulations met the standard requirements for oleogels, with the most favored being Formula F3, which includes 1% watermelon rind extract and 3% orange peel essential oil. This research highlights the potential of watermelon rind extract and orange peel essential oils as effective nutrients for hair loss treatment.